JUSTICE VALUE APPROACH IN THE REFORM OF DETERMINING THE SALE VALUE OF TAX OBJECTS TO STRENGTHEN REGIONAL FISCAL CAPACITY - Sri Rahayu (Proceeding International Conference on Social Sciences, 2026)
This study aims to analyze the application of fairness values in reforming the determination of Taxable Object Sales Values (NJOP) as a strategic effort to strengthen regional fiscal capacity. The determination of NJOP has been guided by Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. However, its implementation in many regions does not reflect fair market value and is not in line with the principle of fairness as mandated by Article 23A of th e 1945 Constitution and the principle of justice in tax collection. This research uses a normative juridical method with a statutory, conceptual, and comparative approach to the regulations for assessing the Taxable Object Sales Value (NJOP) in several regions that have updated their land and building value databases. The research data was obtained through literature studies, regulatory reviews, and analysis of taxable object assessment practices based on the derivative provisions of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regi onal Governments, including the Minister of Finance Regulation concerning assessment guidelines. The research results show that the integration of the principles of fairness, transparency of assessment, and regular data updates in the Taxable Object Sales Value (NJOP) regulation has been proven to increase the contribution of Land and Building Tax to Regional Original Revenue (PAD) and strengthen regional fiscal capacity. Furthermore, the implementation of objective market-based assessments as mandated by Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments can reduce tax disparities between taxpayers and increase the legitimacy of regional tax collection. This research recommends the reconstruction of the Taxable Object Sales Value (NJOP) regulation through harmonization of regional regulations with Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, strengthening regional government assessment standards, and digitizing the land value information system to realize sustainable and equitable tax collection.